Uptake of intrauterine contraception after medical management of first trimester incomplete abortion: A cross-sectional study in central Uganda - Herbert Kayiga; Emelie Looft-Trägårdh; Amanda Cleeve; Othman Kakaire; Nazarius Mbona Tumwesigye; Musa Sekikubo; Joseph Rujumba; Kristina Gemzell-Danielsson; Josaphat Byamugisha (PLoS ONE, 2025)
Background Although intrauterine devices (IUDs) are readily available in Uganda, their utilization remains low, including within post abortion care. The level and factors associated with uptake of post abortion IUDs, are not well documented. We set out to determine the uptake and factors associated with uptake of post abortion IUDs after medical management of first trimester incomplete abortions in central Uganda. Methods Between February 2023 and September 2023, we conducted a cross-sectional study among women aged 15–49 years, who expressed interest in initiating post abortion intrauterine contraception, and were managed with misoprostol for first trimester incomplete abortions at five health facilities in central Uganda. Healthcare providers received extensive training in post abortion contraceptive counselling and service provision. Data from 650 participants were collected using interviewer administered questionnaires. The primary outcome was uptake of post abortion IUDs, defined as the actual insertion of the post abortion IUDs. Data were collected during a post abortion follow up visit. The determinants of post abortion IUD uptake were assessed using the modified poisson regression. Results The prevalence of post abortion IUD uptake among all women assessed was 370/1911 (19.4%; 95%CI 17.7–21.2). The prevalence of IUD acceptors among those who accepted any form of contraceptives was 370/650 (56.9%; 95%CI 53.1–60.7). Among the other available contraceptive choices, 121(18.6%) women opted for injectable Depo-Provera (DMPA), 116(17.9%) women opted for implants, 35(5.4%) women opted for oral contraceptive pills, 5 (0.8%) of the women opted for condoms, and 3 (0.5%) women for periodic abstinence. The median age of the participants was (27 ± IQR 30, 23) years. The majority of the participants who had had abortions were living with a partner (84.0%). A third of the participants who had had abortions, had 2−3 children. Nearly 60% of IUD users, opted for the copper IUDs. The post abortion IUD uptake was independently associated with religion- being a Pentecostal (Adjusted PR = 2.49, 95%CI= (1.19–5.23), p-value = 0.016), monthly earning > one million Ugx (270 USD) (Adjusted PR = 1.88, 95%CI= (1.44–2.46), p-value<0.001), and staying <5 kilometres from the health facility (Adjusted PR = 1.34, 95%CI= (1.04–1.72), p-value = 0.023). Women who were not cohabiting with their partners, were less likely to choose IUDs (Adjusted PR = 0.59, 95% CI= (0.44–0.79), p-value = 0.001). Conclusion The uptake of IUDs among post abortion women was nearly 60% emphasizing the potential impacts of integrated contraceptive services in Post abortion care. The impact of comprehensive and updated training on post abortion contraceptive counselling, is vital on the uptake of IUDs. Regardless of sociodemographic status, women seeking post abortion care in Uganda should be provided with high-quality integrated services by trained providers offering a range of contraceptive methods. Such efforts may not only prevent unintended pregnancies but also improve health equity across the country.